Centrifugal gravity-induced BMP4 induces chondrogenic differentiation of adipose-derived stem cells via SOX9 upregulation. Issue 1 (December 2016) - Jang, Yeonsue; Jung, Hyerin; Nam, Yoojun; Rim, Yeri; Kim, Juryun; Jeong, Sang; Ju, Ji
Abstract Background Cartilage does not have the capability to regenerate itself. Therefore, stem cell transplantation is a promising therapeutic approach for impaired cartilage. For stem cell transplantation, in vitro enrichment is required; however, stem cells not only become senescent but also lose their differentiation potency during this process. In addition, cytokines are normally used for chondrogenic differentiation induction of stem cells, which is highly expensive and needs an additional step to culture. In this study, we introduced a novel method to induce chondrogenic differentiation of adipose-derived stem cells (ASCs), which are more readily available than bone marrow-derived mesenchymal stem cells(bMSCs), using centrifugal gravity (CG). Methods ASCs were stimulated by loading different degrees of CG (0, 300, 600, 1200, 2400, and 3600 g) to induce chondrogenic differentiation. The expression of chondrogenic differentiation-related genes was examined by RT-PCR, real-time PCR, and western blot analyses. The chondrogenic differentiation of ASCs stimulated with CG was evaluated by comparing the expression of positive markers [aggrecan (ACAN) and collagen type II alpha 1 (COL2A1)] and negative markers (COL1 and COL10) with that in ASCs stimulated with transforming growth factor (TGF)-β1 using micromass culture, immunofluorescence, and staining (Alcian Blue and Safranin O). Results Expression of SOX9 and SOX5 was upregulated by CG (2400 g for 30 min). Increased expression of ACAN and COL2A1 (positive markers) was detected in monolayer-cultured ASCs after CG stimulation, whereas that of COL10 (a negative marker) was not. Expression of bone morphogenetic protein (BMP) 4, an upstream stimulator of SOX9, was upregulated by CG, which was inhibited by Dorsomorphin (an inhibitor of BMP4). Increased expression of proteoglycan, a major component of cartilage, was confirmed in the micromass culture of ASCs stimulated with CG by Alcian Blue and Safranin O staining. Conclusions Chondrogenic differentiation of ASCs can be induced by optimized CG (2400 g for 30 min). Expression of SOX9 is upregulated by CG via increased expression of BMP4. CG has a similar ability to induce SOX9 expression as TGF-β1.